1998
DOI: 10.2337/diabetes.47.12.1836
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glutamine:fructose-6-phosphate amidotransferase by cAMP-dependent protein kinase.

Abstract: Glutamine:fructose-6-phosphate amidotransferase (GFA) is the rate-limiting enzyme in hexosamine biosynthesis, an important pathway for cellular glucose sensing. Human GFA has two potential sites for phosphorylation by cAMP-dependent protein kinase A (PKA). To test whether GFA activity is regulated by cAMP-dependent phosphorylation, rat aortic smooth muscle cells were treated in vivo with cAMP-elevating agents, 10 micromol/l forskolin, 1 mmol/l 8-Br-cAMP, or 3-isobutyl-1-methylxanthine. All treatments resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 0 publications
4
57
1
Order By: Relevance
“…We also observed no high glucose effect on the amount of UDP-GlcNAc, while in other reports a hyperglycemia-induced increase in UDP-GlcNAc concentrations in skeletal muscle has been described (41,42). However, the flux through the HBP is tightly regulated-GFAT activity is inhibited in an autocrine feedback loop by UDP-GlcNAc (13) and GlcN-6-P (43) and is posttranslationally modified by protein kinase A phosphorylation (44). A recently described striated muscle-specific splice variant of GFAT exhibits a markedly increased susceptibility to inhibition by UDP-GlcNAc (45).…”
Section: Discussionmentioning
confidence: 54%
“…We also observed no high glucose effect on the amount of UDP-GlcNAc, while in other reports a hyperglycemia-induced increase in UDP-GlcNAc concentrations in skeletal muscle has been described (41,42). However, the flux through the HBP is tightly regulated-GFAT activity is inhibited in an autocrine feedback loop by UDP-GlcNAc (13) and GlcN-6-P (43) and is posttranslationally modified by protein kinase A phosphorylation (44). A recently described striated muscle-specific splice variant of GFAT exhibits a markedly increased susceptibility to inhibition by UDP-GlcNAc (45).…”
Section: Discussionmentioning
confidence: 54%
“…However, the effect was not normalized to their standard conditions except the depletion or addition of the PKA. The stimulation of GFAT from rat aortic smooth-muscle cells via in i o induction of endogenous PKA has also been shown by Zhou et al [10]. This activation was approx.…”
Section: Regulation Of Gfat Activity By Pka Phosphorylationmentioning
confidence: 63%
“…In B. emersonii protein phosphatases 2A and 2C are involved in this process [9]. The stimulation of rat GFAT by protein kinase A (PKA) has been demonstrated in i o and in itro [10]. However, the K i value for the feedback inhibitor UDPNG was not altered by PKA treatment of GFAT, suggesting that PKA is not involved in the feedback regulation of GFAT mentioned above.…”
Section: Introductionmentioning
confidence: 98%
“…Also, the unique tissue distribution makes GFAT1-L a very interesting target for further research on the tissue-specific regulation of hexosamine generation and the potential link to insulin resistance. Zhou et al (1998) have shown that GFAT1 activity is regulated through phosphorylation by cAMP-dependent protein kinase A (PKA). Human GFAT1 contains two potential PKA phosphorylation sites.…”
Section: Cloning Of a Novel Gfat1 Splice Variantmentioning
confidence: 99%
“…The GFAT1-L open reading frame consists of 2097 nucleotides, encoding a 699-aminoacid protein with a predicted molecular mass of 78790.38 Da (GFAT1: 2043 bp, 681 amino acids, and 76743.22 Da). The GFAT1-L insertion occurs within a sequence corresponding to a hinge region in the GFAT1 protein (Zhou et al 1998). …”
Section: Cloning Of a Novel Gfat1 Splice Variantmentioning
confidence: 99%